Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
there is one solution:
use elimination method
5x - 7y = 12
5y - 2x = -7 ---> change equation around
5x - 7y = 12
-2x + 5y = -7
2 x ( 5x - 7y) = 2 x (12) multiply both sides by 2
5 x (-2x +5y) = 5 x (-7)
this give you
10x - 14y =24
-10x+25y = -35 add down
-----------------------------
11y = - 11 x is eliminated to find y value
y = -1 input to one of the original equations
5(-1) - 2x = -7
-5 - 2x = -7
+5 +5 add 5 to both sides
----------------------------
-2x = -2
x = 1
your coordinates for when they intersect is at (1, -1)
one solution
use elimination method
5x - 7y = 12
5y - 2x = -7 ---> change equation around
5x - 7y = 12
-2x + 5y = -7
2 x ( 5x - 7y) = 2 x (12) multiply both sides by 2
5 x (-2x +5y) = 5 x (-7)
this give you
10x - 14y =24
-10x+25y = -35 add down
-----------------------------
11y = - 11 x is eliminated to find y value
y = -1 input to one of the original equations
5(-1) - 2x = -7
-5 - 2x = -7
+5 +5 add 5 to both sides
----------------------------
-2x = -2
x = 1
your coordinates for when they intersect is at (1, -1)
one solution
5x - 7y = 12
5y - 2x = -7
5x - 7y = 12
-2x + 5y = -7
3x + 2y = 5
3(2) + 2(-1) = 5
6 + (-1) = 5
6 - 1 = 5
5 = 5
5y - 2x = -7
5x - 7y = 12
-2x + 5y = -7
3x + 2y = 5
3(2) + 2(-1) = 5
6 + (-1) = 5
6 - 1 = 5
5 = 5
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.